2017
DOI: 10.5123/s1679-49742017000100014
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento, atitude e prática dos vacinadores sobre vacinação infantil em Teresina-PI, 2015*

Abstract: a high number of inadequate answers related to knowledge and attitude and of adequate answers concerning practice were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
6
0
12
Order By: Relevance
“…Ressalta-se que não há consenso na literatura quanto à pontuação a ser considerada satisfatória para que os escores do questionário CAP sejam entendidos como adequados. Então, assumindo que os estudos ponderam uma variação na porcentagem de acertos entre 50 7 e 90%, 9 somaram maiores pontuações os profissionais que participaram do curso de formação para CIHDOTT (p=0,047) e entre os que não identificaram empecilhos para desenvolver o trabalho (p=0,015). Quanto à atitude, os menores escores estão entre os profissionais que têm vínculo empregatício em outra instituição (p=0,027).…”
Section: Resultsunclassified
“…Ressalta-se que não há consenso na literatura quanto à pontuação a ser considerada satisfatória para que os escores do questionário CAP sejam entendidos como adequados. Então, assumindo que os estudos ponderam uma variação na porcentagem de acertos entre 50 7 e 90%, 9 somaram maiores pontuações os profissionais que participaram do curso de formação para CIHDOTT (p=0,047) e entre os que não identificaram empecilhos para desenvolver o trabalho (p=0,015). Quanto à atitude, os menores escores estão entre os profissionais que têm vínculo empregatício em outra instituição (p=0,027).…”
Section: Resultsunclassified
“…The results showed that less than half (43%) of vaccination rooms had at least one trained professional less than two years old. 28 The absence of PE is a reality that compromises the change in vaccination practices. A study conducted in the Extended Western Region of Minas Gerais also corroborates these findings.…”
Section: Vaccination In Everyday Life and Permanent Educationmentioning
confidence: 99%
“…In addition to advances in the field of immunization, there are the particularities of each immunobiological and the overload of work that require PE to professionals working in a vaccination room. 6,28 The beginning of the work in the vaccination room requires a previous knowledge about the immunobiological agents, either by means of knowledge already acquired or by the accomplishment of qualification of the professional, however not always this process of training. Professionals are predominantly entered into vaccination rooms without prior training and learn about day-today vaccinations with other professionals.…”
Section: Vaccination In Everyday Life and Permanent Educationmentioning
confidence: 99%
“…Outros estudos também destacam a falta de preparo dos profissionais vacinadores em relação às suas atividades na sala de vacina e enfatizam essa deficiência como um grande desafio nos serviços de saúde, visto que as inadequadas práticas de vacinação podem causar danos aos usuários e comprometer a qualidade e credibilidade dos imunobiológicos (13,14) .…”
Section: "Quando a Criança Vem Fazer A Vacina A Mãe é Informada Da Runclassified